Design and Manufacture of a Cable Feed-Through Part in Carbon Composite - Viljakainen, Arttu (My University, 2024)
At CERN, the center of nuclear physics research in Europe, there is the largest and most powerful particle collider in the world, the Large Hadron Collider (LHC). LHC is the last link in a chain of particle accelerators taking the accelerated particles up to 99.9999991 % of lightspeed. The particles are not only accelerated in the LHC, but they are also collided into each other. The particles go round the LHC in two beams going in opposite directions. The beams are then collided in four different collision points around the 27-kilometer circumference. One of these points is located inside the detector called Compact Muon Solenoid (CMS). CMS is a solenoid-based detector, designed to study high energy collisions. During the next long shutdown of the LHC, the Long Shutdown 3 (LS3), LHC is to be upgraded to increase the number of collisions. The new and more powerful HL-LHC (High Luminosity LHC) means that the CMS is going through upgrades as well. The upgrades include the complete redesign of the inner parts of the tracker, to achieve higher resolution. The inner parts of the tracker are divided into two regions, the barrel region and the end cap region. The outer part of the barrel region is referred to as the TB2S (Tracker Barrel with 2S-modules). It contains two-sided silicon strip tracker modules, designed for particle tracking. The 2S-modules are attached to ladder structures, which form multiple overlapping layers of sensors, efficiently surrounding the collision point. The services, like electricity and cooling are routed to the 2S-modules through the ladder front panel. The front panel needed to be designed from scratch to house all the needed connectors for the services. The ladder structure is made of carbon-fiber composite c-profiles. Carbon-fiber reinforced composites are the chosen material for the detector’s inner structures, due to its strength, radiation resistance and low density. The front panel was also designed to be made of carbon-fiber composite, so that different thermal expansion coefficients would not impose problems. The production method was chosen as the SMC/BMC ((Bulk Molding Compound/ Sheet Molding Compound). The material is either as a bulk molding compound (BMC) or as sheets (SMC) and it has the fibers and the matrix already combined. The material is inserted into a preheated mold that is then closed with high pressure. Due to high temperature and pressure the material hardens into the shape of the mold. The aim for this study is to find the correct parameters for the molding process to produce parts of acceptable quality, reliably. The initial values for the parameters are found in existing literature. The parameters were then tuned in between the molding cycles, based on the results of previous tests. Acceptable quality was achieved after thirty-five iterations and confirmed with twenty additional parts. The manufacture of the additional parts was then used to estimate the time needed to produce the full patch of parts.

Euroopan hiukkasfysiikan tutkimuskeskuksessa Cernissä sijaitsee maailman suurin ja tehokkain hiukkastörmäytin nimeltään LHC (Large Hadron Collider). LHC on hiukkaskiihdytinketjun viimeinen linkki, jossa kiihdytettävät hiukkaset saavuttavat jopa 99,9999991 % valonnopeudesta. LHC ei kuitenkaan toimi pelkästään hiukkaskiihdyttimenä, vaan on ennen kaikkea hiukkastörmäytin. Hiukkaset ohjataan LHC:n kehälle kahtena vastakkaisiin suuntiin kiertävänä suihkuna. Suihkut törmäytetään neljässä siihen tarkoitetussa pisteessä törmäyttimen 27 km pitkällä kehällä. Yksi näistä pisteistä sijaitsee CMS (Compact Muon Solenoid) -nimisen detektorin sisällä. CMS on solenoidiin perustuva, suuren energian törmäysten tutkimiseen kehitetty laite. LHC:n seuraavan pitkän toimintakatkon aikana se aiotaan päivittää ainakin neljä kertaa tehokkaammaksi. Uusi, tehokkaampi LHC vaatii myös detektorien uudistamista vastaamaan uusia vaatimuksia. CMS:n kohdalla detektorin sisin osa on suunniteltu kokonaan uusiksi suuremman resoluution saavuttamiseksi. Detektorin sisin osa on jaettu kahteen alueeseen, tynnyrialueeseen (the Barrel region) ja päätyalueeseen (the End Cap region). Tynnyrialueen ulompaa kerrosta kutsutaan nimellä TB2S (Tracker Barrel with 2S modules). Se koostuu hiukkasten jäljittämiseen suunnitelluista 2S-moduuleista, jotka koostuvat kahdesta piinauhajäljittäjäsensorista (Silicon strip tracker). 2S-moduulit kiinnitetään tikasmaisiin tukirakenteisiin, jotka asetetaan useana kerroksena tynnyrialueelle, jotta saadaan katettua mahdollisimman tehokkaasti koko törmäyspistettä ympäröivän alueen. Tikkaiden etupaneelin kautta ohjataan 2S-moduuleille niiden tarvitsemat ”palvelut”, kuten sähköenergia, tiedonsiirtokanava ja jäähdytys. Etupaneeli oli siis suunniteltava pitäen silmällä näiden läpivientien erityistarpeita. Tikasrakenne valmistetaan hiilikuitukomposiitista valmistetuista c-profiileista. Hiilikuitukomposiitti on valittu sisäosien rakenteellisten osien materiaaliksi sen vahvuuden, säteilynkestävyyden ja pienen tiheyden vuoksi. Etupaneeli päätettiin valmistaa myös hiilikuidusta, jotta vältyttäisiin eriävien lämpölaajenemiskerrointen aiheuttamilta ongelmilta. Valmistusmenetelmäksi valittiin BMC/SMC (Bulk Molding Compound/ Sheet Moulding Compound). BMC/SMC -menetelmässä materiaali on joko massana (BMC) tai levyinä (SMC) ja se sisältää matriisiaineen (hartsi) ja vahvisteen (hiilikuitusäikeet) valmiiksi sekoitettuna. Materiaali asetetaan valmiiksi lämmitettyyn muottiin, joka puristetaan kiinni suurella paineella. Paineen ja lämmön alaisena hartsi kovettuu ja kappale saa muotonsa. Tämän tutkimuksen tavoitteena oli löytää oikeat prosessiparametrit hyväksyttävän laadun saavuttamiseksi luotettavasti. Parametrien haku aloitettiin kirjallisuudesta löytyneiden arvioiden perusteella päätetyistä lähtöarvoista. Arvoja säädettiin osien valmistamisen välissä, silmämääräisen virheenarvioinnin perusteella. Hyväksyttävä laatu saavutettiin 35 kokeilukappaleen valmistamisen aikana. Prosessin viimeistelyn jälkeen arvioitiin tarvittavan osamäärän valmistamiseen vaadittava aika valmistamalla vielä kaksikymmentä kappaletta tasaisella tahdilla.
Keywords: CERN, LHC, CMS Phase 2 Upgrade, carbon fiber reinforced composites, compression molding, TB2S front panel